Low-grade hemodilution improves the microcirculatory function in surgical patients - Hahn, Robert G; Tlapakova, Katerina; Koudelova, Hana; Knoblochova, Veronika; Rehak, David; Cerny, Vladimir; Astapenko, David (Microvascular research, 2025)
BACKGROUND: Excess fluid in the interstitium can adversely affect the microcirculation. We studied how gradual dilution of the blood plasma by crystalloid fluid influences microcirculatory variables and capillary filtration in 20 patients undergoing surgery. METHODS: Video recordings of the sublingual mucosal were made on four occasions during the surgery and compared with quasi-measurements of the capillary filtration rate using retrospective volume kinetic data collected over 5-10-minute periods during 262 infusion experiments with crystalloid fluid. RESULTS: The number of crossings (vessel density) increased up to plasma dilution of 15-20 % whereafter it decreased. The proportion of the vessels that were perfused (PPV) decreased and reached a nadir of -15 % at a dilution of 20-30 %. Changes in the number of crossings and the PPV correlated (r = 0.62, P < 0.001) but the curve was displaced so that crossings showed no change when PPV had decreased by approximately 10 %. However, the PPV of vessels with a thickness of ≤25 μm increased or remained constant in the dilution range of up to 20 %. The volume kinetic analysis showed that the capillary filtration was greater than expected from proportionality with the volume expansion up to a plasma dilution of 15 %, the greatest difference (+89 %) being for plasma dilution up to 5 %. CONCLUSION: Plasma dilution of up to 15 % increased the vessel density, and the capillary filtration increased by more than suggested by the volume expansion. Dilution >15 % had a negative influence on these variables.
Keywords: Plasma dilution; dospělí; Crystalloid fluid; retrospektivní studie; Humans; lidé středního věku; Middle Aged; Hemodilution; Regional Blood Flow; Crystalloid Solutions; kapilární permeabilita; Time Factors; Microcirculation; mužské pohlaví; Mouth Floor; krystaloidní roztoky; Adult; ústní spodina; regionální krevní průtok; mikrocirkulace; výsledek terapie; hemodiluce; časové faktory; Kinetics; ústní sliznice; Treatment Outcome; Microvessel density; ženské pohlaví; kinetika; Capillary Permeability; lidé; Aged; senioři; Male; Retrospective Studies; Mouth Mucosa; Pharmacokinetics; Female